LOW BACK PAIN - Andaru Cahya S; Widodo Mardi Santoso; Machlusil Husna; Badrul Munir; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2021)
Low back pain is the most common symptom found in the primary health care and is the number one cause of disability throughout worldwide. It is estimated that around 60 â€“ 80% the world population will experience back pain during their lifespan. There are three different source of pain in the spine: axial-lumbosacral, radicular and reffered pain. All of these source brings different clinical presentations. Low back pain could be classified as acute, subacute and chronic low back pain. The pain could be nociceptive or neuropathic, the most common symptoms reported are â€œpressure painâ€ and â€œpain attackâ€.Â The physician should be aware of â€œred flagsâ€ symptoms that lead into more serious condition beside back pain and, therefore the patient has to be investigated to further examination whenever these symptoms present. The management of low back pain consist of severe modalities, both therapeutic and rehabilitative procedure. Oftentimes, the management needed multidisciplinary approach. It is important to general practitioners to identify and treat low back pain appropriately to reduce the burden of the disease and to prevent the disabilties caused by this condition.